Radiosurgery for Metastatic Spinal Tumors: Follow-Up MR Findings - Hwang, Y.J.; Sohn, M.-J.; Lee, B.H.; Kim, S.Y.; Seo, J.W.; Han, Y.H.; Lee, J.Y.; Cha, S.J.; Kim, Y.H. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: We reported the MR findings of spinal metastatic lesions after SRS according to the volumetric changes (in press). However, in the case of osteoblastic metastatic lesions, tumor volume usually doesn't change during remission. In this study, we retrospectively analyzed pre- and post-SRS CT and MR imaging findings of locally controlled osteoblastic spinal metastatic lesions besides volumetric changes MATERIALS AND METHODS: Among 113 spinal metastatic lesions in 72 patients, 10 lesions were osteoblastic. CT and MR images were reviewed to identify 4 parameters: 1) changes in tumor volume, 2) changes in CT attenuation, 3) changes in T2 signal intensities and 4) changes in degrees of contrast enhancement. RESULTS: Tumor volume was unchanged in 9 lesions and increased in 1 lesion. CT attenuation increased in 7 lesions and T2 signal intensities were heterogenous with dark signal foci within the tumor in 3 of 7 lesions and with dark and bright signal foci within the tumor in 4 of 7 lesions. In 3 lesions where CT attenuation decreased, T2 signal intensity became heterogenous with dark and bright foci in 2 of 3 lesions and T2 signal intensity became normalized in 1 lesion. The degree of contrast enhancement decreased in 8 lesions but 2 lesions showed persistent contrast enhancement. CONCLUSIONS: Further progression of sclerotic changes was a more common finding than loss of sclerotic foci. Main MR imaging features of osteoblastic lesions after treatment were development of dark with or without bright signal foci, with decrease in contrast enhancement. EBRTexternal beam radiation therapySRSstereotactic radiosurgery